Analysis of the Relationship between Lifestyle and Adaptation of Adolescents in Islamic Boarding Schools in East Java - Sulika, Erni; Qurota’Ayun, Henny; Utami, Sri; Dwisatyadini, Mutimanda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Skin diseases remain a common health problem in boarding school environments, particularly among tensth-grade students who are undergoing early adolescent adaptation. Communal living conditions, high occupancy density, and limited personal care practices increase the risk of skin disorders such as acne and scabies. This study aimed to analyze the pattern of skin disease occurrence and the response to treatment using Mikania micrantha, with particular attention to lifestyle factors and adolescent adaptation in an Islamic boarding school in East Java. A descriptive quantitative approach with an observational design was employed. Data were obtained from health records of female tenth-grade students who experienced skin disorders and received topical treatment using Mikania micrantha. Descriptive analysis was conducted to examine case distribution and treatment outcomes. The findings indicate that acne and scabies were the most prevalent skin conditions among students. The use of Mikania micrantha showed generally positive responses; however, treatment effectiveness was closely related to environmental conditions and hygiene behaviors. This study highlights the importance of an integrative approach combining traditional herbal treatment, environmental management, and the promotion of clean and healthy living behaviors to address skin health issues among adolescents in boarding school settings.